2008
DOI: 10.1155/2008/534372
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Compliance with Continuous Positive Airway Pressure in Patients with Obstructive Sleep Apnea

Abstract: BACKGROUND: Continuous positive airway pressure (CPAP) is an effective treatment for obstructive sleep apnea (OSA). However, compliance is a significant problem and has been incompletely assessed in long-term studies.OBJECTIVE: To assess the long-term compliance of OSA patients with CPAP therapy.SUBJECTS: Eighty patients who had had a diagnosis of OSA at least four years previously and received a written prescription for CPAP were evaluated.METHODS: Subjects were identified by reviewing sleep laboratory record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
109
3
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(130 citation statements)
references
References 30 publications
(34 reference statements)
10
109
3
8
Order By: Relevance
“…Our study selected a group of subjects with OSA who experienced problems with nasal-oral adverse effects during the first night of a CPAP trial. Prior studies have shown that the most common reason for not initiating CPAP is general displeasure or discomfort with the CPAP device during the CPAP titration trial 17 or during the first night of therapy. 2 We aimed to improve the symptoms related to CPAP early in this group rather than waiting for nasopharyngeal symptoms to occur later after the use of CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…Our study selected a group of subjects with OSA who experienced problems with nasal-oral adverse effects during the first night of a CPAP trial. Prior studies have shown that the most common reason for not initiating CPAP is general displeasure or discomfort with the CPAP device during the CPAP titration trial 17 or during the first night of therapy. 2 We aimed to improve the symptoms related to CPAP early in this group rather than waiting for nasopharyngeal symptoms to occur later after the use of CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…9 Self-reported PAP compliance (i.e., use among those with OSA), which was similar between participants with and without past-year AHI (83.0% and 81.2%, respectively), was higher than objectively determined compliance reported in the general population, which is between 40% and 60% one year after starting PAP. 34,35 Differences in assessment method may explain this discrepancy since patient self-report of PAP compliance is generally higher than compliance based on electronic data downloaded from PAP machines. 36 However, it is also possible that this population is more compliant in general, or was more compliant than usual in the immediate period leading up to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…5 Adverse effects are common, [6][7][8][9][10] and overall adherence to CPAP therapy is poor, because patients often abandon therapy within the first month. [11][12][13][14] The monitoring of CPAP therapy is now possible with the advent of CPAP machines that gather statistical and graphical information on use and efficacy. Current CPAP machines collect data on time-at-pressure, apneas, hypopneas, snoring, and leaks, and those data are important in clinical follow-up, especially if the patient initiated on auto-titrating CPAP, without polysomnographic titration.…”
Section: Introductionmentioning
confidence: 99%